Diseño y construcción de un prototipo de monitoreo remoto de señales biomédicas fundamentales para pacientes estacionarios - Caisatoa Chulca, Mayra Elizabeth (2018)
The present project is a prototype for the monitoring of biomedical signals of blood pressure, blood oxygenation and heart rate of patient who is not in movement. This device allows to visualize and obtain the results to them remotely and register the information in a database automatically. In additional, a system alert was included for the early detection of events of the signals, by the sending of emails to the doctor. The first chapter describe the technical project background, which includes problem statement, justification, the general and specifics objectives. The second chapter details the theoretical framework used for the development of the project. The concepts of the biomedical signals of blood pressure, blood oxygenation and heart rate, the methods implement in each signal, the stages of acquisition and digitization of biosignals, the concept of monitoring, the applicable standards in electronic medical equipment, etc. The third chapter shows the design of each of the stages of the device like: the elements used, the circuits of each biomedical signal, the programming in the development platform and the results of the remote control. Finally, in the last chapter will present the tests that they made sure the correct operation of the prototype and the errors obtained also is calculate.